Internet-Based Lifelong Learning: Implications for Language Teaching and Semiotic Structure Principles in Media Sociology and Religion Sociology - Vindigni, Giovanni (Archives of Business Research, 2023)
In the course of science theory, when we deal with the subject of language teaching in the context of semiotic structure principle developments as well as in the course of the media culture and religious sciences, it shows that in numerous contributions concerning this subject area there is a complaint that the aporetic treatment and integration of language and religious history [Sprachgeschichte/Religionsgeschichte] in the sense of an internal and external language and religious history should be taken into account [1]. The associated diachrony of historical linguistics is said to be not only relevant but also sufficiently socially systemic and imminently codependent for its constitution [2]. There is talk of a "step child," of "marginal permanence," and even of a malicious deletion from facultative curricula since the international history of language and language teaching is said to be hardly fruitful, especially in view of a problem-oriented approach, obviously not having any relevance for the present constantly transforming, media- and religion-sociology-oriented reality of life and work (paper presented at the Ecumenical and Pedagogy of Religion Colloquium, "Dimensions of Education," at the Nicolaus Copernicus University in Torun, on October 11, 2007, in Torun). The author of this paper does not wish to join in this lament about the "Geschichtslosigkeit und Religionslosigkeit" [historical unawareness] regarding time and language, with its sustainable effect on international language and religion teaching, since in recent years, there have been some astonishing changes in perspective, signaling a big opportunity in terms of a substantial paradigm shift for international language teaching – the subject of lifelong learning.